Medya siyaset ilişkisinde lider kimliği - Temel, Ahmet Ziya (My University, 2002)
Mutlu olmayı öğrendiğimizde ve mutluluğumuzu umudun ışığında diğerlerine geçirdiğimizde, mutlu sona ulaşmaya layık olacağız. Yüzyıllar boyunca çok çarpıcı insanlar çıkmış, bu insanlar insanlığın refahı için savaşan nesilleri temsil etmişlerdi. Bu insanlar farklı özelliklere sahipti. Bazen korku salıyor, bazen de hırs aşılıyorlardı insanlığa. Hala akıllardan silinmiş değiller Eskiden, düşüncelerini yayan ve bu düşünceleri kontrol etme isteğinde olan bir lider profili varken, bugünün dünyasında çeşitli kitle iletişim araçlarını kullanarak toplumdaki her gruba ve her bireye erişme imkanına sahip bir lider profiliyle karşı karşıyayız. Geçmişten günümüze toplanan medeniyetlerin zenginliğini bir bütün olarak gelecek nesillere aktarmak bireylerin temel sorumluluklarından biridir. İçlerinden biri çıkar ve bu elbiseyi giymeye çalışır. Birilerinin giydiği veya birilerine giyindirilmeye çalışılan bu özel görev günümüzde kitle iletişim araçları tarafından yapılmaktadır. Kitle iletişim araçlarının lider kimliği oluşturmada etkisi nedir? Eğer varsa bu etkinin gücü nedir? Bu çalışma, bu soruların cevabını bulmaya yönelmeye çalışmıştır. Çalışma dört ana bölümden oluşmaktadır. Birinci bölümde, iletişim fikri , iletişim araçlarının tanımlanması, bunların etkisi, fonksiyonları, halkla ilişkiler, propaganda ve reklamcılıkla ilgilidir. İkinci bölüm liderlik fikrine dayanmaktadır. Lider nedir? Lider kime denir? Çıkış nedenleri nelerdir? Bir liderin özellikleri ve görevleri nelerdir?Bu bölümde bu tip sorulara cevap aranmıştır. Üçüncü bölümde kitle iletişim araçlarının siyasal iletişimle bağlantısı ile birlikte medya gücünün dayandığı kaynaklar araştırılmaya çalışılmıştır. Medyanın gücü, bu gücün topluma ve siyasete etkisi düşünürlerin fikir dünyasında tartışılmıştır. Dördüncü bölüm medya ile liderlik arasındaki ilişkiler yumağının Türkiye'deki durumuna bakılmıştır. Dünyadaki diğer devletlerden ayrı olarak, cumhuriyetlerin kuruluşundan bugüne gelişimi ortaya konmuştur. Günümüzün dünyasının bir gerçeğidir ki, medya her geçen büyüyen gücünü lider yaratmada kullanma gayreti içindedir. Medya bir güçtür ve medya bu gücü hakkıyla kullanmalıdır. Medya bir lider yaratabilir mi? Bir lider yaratma isteği toplumları ne kadar etkileyebilir? Bu çalışmada bu sorulara cevap aranmaya çalışılmıştır.

As we learn to be happy, and to pass on ouur happiness to others through a light of hope, we will deserve to reach a happy end. Throughout the centuries, there has been many outstanding people, who have represented generations of struggle. They had variable characters sometimes spreading fear, sometimes enthusiasm, many of whom are still in the minds of people From a laeder profile who spread his set of ideas and the will of control to the largest extend of his reachin the old times, we now face a leader profile who reaches to each and every group in the society by using the variours mass communication tools available in today's world. One of the basic responsibilities of individuals is to achieve a complete tansfer of the civilization accumulated throughout the history, to the future generations But do individuals give their faith and commitment to the ones who fit to their longins and to the dressed up ones who give their hands. Apart from the personel probability of success of the dressed up charactersfacing their society, do mass communication tools also contribute to the lieder identity? İf so what is the extend of this conribution? This study intends to provide an answer to a reality from the past to the future. Who is a laeder? Where excatly is laedership positioned relative to personel gifts of some individuals and to the lines of history marked up by certain events? What is the contribution of the leader to these mentioned lines? Of the four main parts of the study, the first part is about the communication concept; definition of mass communication tools; their effects, functions; public relations, propaganda and advertising. The second part is based on the consept of leadership. What is a leader? Who is called a leader? What are the reaons of its emergence? What are the types of leader ship? What are the features and duties of a leader? Are some of the questions intended to be answered in this part. The third part investigates the conformity of the mass communication tools and leadership identity taking into account the political communication, public relations, advertising and propaganda. The power of media, the origin of this power, its influance on the society and impact on politics is discussed within the framework of the ideas of the philosophers The fourth part focuses on the relationship between media and leadership in Turkey. Apart from the developments taking place on the world, what are the improvements in media-politics relations? Those issues are mentioned starting from foundation of the Republic up to date. It is a reality in today's world that tha effectiveness of media is increasing rapitlymarking, who ever it wishes, a leader. İn addition media has become such a significant power that it is pushing its way to beingthe top power from its current position as being the 4th power. Media is power, and the users of media are representing the power. Can amedia create a leader ? What is the influance of media on the way of the ones who are willing to be leaders? What kind of a power is media? For whom does it exercise its power? Are some of the questions to be answered.
Keywords: Liderlik; Medya Siyaset